The Use of Econometric Methods in Family Farm Succession Studies - Bohak, Zarja; Borec, Andreja (Journal for Geography, 2009)
Farm succession is an important issue for any family farm, for the future structure of farming and for rural policy makers. This is the process whereby the skills, traditions and capital of farming are passed from one generation to the next. Scientists realized the importance of scientific investigation of succession on family farms no more than thirty or forty years ago, as the earliest studies bear dates from 1968 on (see i.e. Nalson 1968). There are many different scientific methods used to process surveys’ data or to represent the process of farm succession; this paper offers a review of foreign and Slovene studies from the last 15 years, in which econometric methods are used to describe and analyse the family farm succession process.